Spaceborne signals of opportunity for reflectometry and scatterometry - Isaksson, Frans-Erik; Bennet, Patrik (My University, 2020)
This master’s thesis is carried out in two main parts. The first part is a compilation of literature studies of the general passive reflectometry and scatterometry principles, techniques, capabilities and needs. The second part, motivated by arguing the results of the previous, consists of an implemented agriculture soil moisture PAssive Reflectometry and Interferometry System (PARIS) experiment using Ku-band TV Direct Broadcasting Satellite (TV-DBS) opportunity signals. It includes the definition of the experiment setup as well as the derivation of a system model indicating the expected performance. It also covers the process of designing, implementing and verifying the PARIS RF hardware front-end and signal processing software, generating the Delay-Doppler Map (DDM) measurement results. The experiment was performed at the World Heritage Grimeton Radio Station where the PARIS was installed at 120 meters height in an antenna tower overlooking the surrounding agriculture. The results show that the Ku-band TV-DBS PARIS is able to clearly detect the signal at all four measurement areas investigated, even when that differs from the expected region of specular reflection. The measurements Signal-to-Noise Ratio (SNR) varies in between about 10 to 24 dB, while the system model expect it to be exponentially distributed around 18.5 dB. The signal scattering is concluded to consist of both significant specular and diffuse parts, possibly allowing for simultaneous measurements of the the whole system antenna beam coverage area independent of the direction of observation. Future prospects of a Ku-band TV-DBS soil moisture PARIS is extrapolated from the experiment results and discussed, with focus put on three thought products - a stationary installation overlooking agriculture, a dronecarried monitoring system as well as a Low-Earth Orbit (LEO) small satellite Earth Observation (EO) constellation.
Keywords: Remote sensing, passive reflectometry, passive scatterometry, spaceborne signals of opportunity, SOOP, soil moisture measurement, passive reflectometry and interferometry system, PARIS, Earth observation, EO, Ku-band reflectometry, TV-DBS opportunity signals, delay-Doppler map, DDM